2014
DOI: 10.1007/8904_2014_347
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Clinic Atlas: Organization of Care for Children with Inherited Metabolic Disease in Canada

Abstract: The variation we identified in the organization of care highlights the need to investigate the association between practice differences and health outcomes for paediatric IMD patients to inform policies that establish equitable access to services that are beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Consistent with a previous report [24], our survey identified variation in the organization of care within Canadian metabolic centres. Although the evidence with respect to the impact of a coordinated team approach on improved outcomes in the treatment of PAH deficiency is very scarce, one Canadian retrospective study reported that a multidisciplinary centralized approach results in better outcomes in terms of improved adherence to the diet, control of blood Phe, and fewer patients lost to follow up [13].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with a previous report [24], our survey identified variation in the organization of care within Canadian metabolic centres. Although the evidence with respect to the impact of a coordinated team approach on improved outcomes in the treatment of PAH deficiency is very scarce, one Canadian retrospective study reported that a multidisciplinary centralized approach results in better outcomes in terms of improved adherence to the diet, control of blood Phe, and fewer patients lost to follow up [13].…”
Section: Discussionsupporting
confidence: 89%
“…Basic laboratory tests; such as blood or urinalysis; can be used in conjunction with clinical evaluation to obtain a differential diagnosis or confirm a diagnosis (7). Meanwhile, the long-term care and treatment of IEM patients involves collaboration of healthcare professionals from multiple disciplines; such as physicians, nurses, pharmacists, dietitians, laboratory practitioners, speech therapists, occupational therapists, dentists, and social workers (8)(9)(10)(11)(12)(13)(14). A multidisciplinary team is essential and crucial to provide IEM patients with better quality health care in terms of treatment, psychological support, and educational resources (15).…”
Section: Introductionmentioning
confidence: 99%